2008
DOI: 10.1111/j.1574-6968.2008.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofpqqgenes ofEnterobacter intermedium60-2G reduces antifungal activity and induction of systemic resistance

Abstract: Enterobacter intermedium 60-2G, a phosphate solubilizing bacterium, has the ability to induce systemic resistance in plants against soft rot pathogen Erwinia carotovora. Glucose dehydrogenase, an enzyme that utilizes pyrroloquinoline quinone (PQQ) as a cofactor, is required for the synthesis of gluconic acid by E. intermedium 60-2G. Here, we report that the pqqA and pqqB genes are required for phosphate solubilization and induced systemic resistance against a soft rot pathogen in tobacco. Mutations in either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 21 publications
2
27
0
1
Order By: Relevance
“…There are reports that plant growth-promoting bacteria are able to solubilize inorganic and/or organic phosphates in soil, which is dependent on the GDH-PQQ holoenzyme activity (22,36). In addition, transfected PQQ genes enhanced the phenotype of MPS in two rhizobacterial strains, Burkholderia cepacia IS-16 and a Pseudomonas sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that plant growth-promoting bacteria are able to solubilize inorganic and/or organic phosphates in soil, which is dependent on the GDH-PQQ holoenzyme activity (22,36). In addition, transfected PQQ genes enhanced the phenotype of MPS in two rhizobacterial strains, Burkholderia cepacia IS-16 and a Pseudomonas sp.…”
mentioning
confidence: 99%
“…Moreover, PQQ-linked GDH was recently shown to be required by Sinorhizobium meliloti for optimal nodulation efficiency and competitiveness on alfalfa roots (4). Several reports claim that the GDH-PQQ holoenzyme is involved in antimicrobial substance production in Pseudomonas fluorescens (17,28,46) and in Enterobacter intermedium (22), respectively. Additionally, it has been reported that PQQ plays a role beyond that of a cofactor of the PQQ-dependent dehydrogenase.…”
mentioning
confidence: 99%
“…The genes responsible for PQQ production have been cloned and sequenced in several bacterial genera, including Pseudomonas, Methylobacterium, Acinetobacter, Klebsiella, Enterobacter, and Rahnella (5,14,17,36,42). In P. fluorescens B16, the PQQ operon is formed by 11 …”
mentioning
confidence: 99%
“…Several studies with bacterial mutants unable to produce PQQ and gluconic acid have demonstrated the intimate relation of the cofactor to phosphate solubilization processes (7,17). Besides its relevant role in P solubilization, PQQ is reported to be a potent growth-promoting factor for bacteria and plants, has antioxidant properties (5), and is directly related to the production of antimicrobial substances (7,14,36) as well as to the induction of systemic plant defenses (17). Hence, the cofactor PQQ has multiple plant beneficial effects.…”
mentioning
confidence: 99%
“…Additionally, other phenotypic properties of the selected bacterial strains including antifungal, chitin degradation, gelatin degradation, and solubilizing phosphate activity were assessed on the detection agar plates, because the microbial properties are known to involve in biocontrol of plant disease and insect (Han et al, 2008;Kim et al, 2008;Martin and Gundersen-Rindal, 2008). The In vitro antifungal activities of the selected strains were tested by dual inoculation on potato dextrose agar (Difco Inc., Detroit, MI) with plant pathogenic fungi Fusarium oxysporum (KACC NO.…”
mentioning
confidence: 99%